PENGARUH PELATIHAN PENGEMBANGAN POSYANDU MELALUI TANAMAN OBAT KELUARGA (TOGA) TERHADAP PENGETAHUAN KADER KESEHATAN - Genatrika, Erza (Kesmas Indonesia, 2018)
The development of a slow posyandu can be an obstacle to the implementation of health development. The number of integrated posyandu currently shows that the posyandu performance is not optimal yet. Level of integrated posyandu in Indonesia (in 2004) that is only about 2.91%. This is apparent in Sidabowa Village, integrared posyandu only about 9.09% (1 of 11 posyandu). One of the dominant factors that affect the condition is the role of health cadres. Health cadres as community counselors should have a good level of knowledge. This study aims to identify the effectiveness of training to increase cadre knowledge about posyandu level and medicinal plants (TOGA). This research uses quasi experiment design method. The sample in this study is health cadres who attended the training. The results of this study indicate that the provision of education through training is effective in improving cadre knowledge (p <0.05).Keywords: Cadre, TOGA, posyandu, sidabowa